Synthesis and Manipulation of Single-Crystalline Lithium Nickel Manganese Cobalt Oxide Cathodes: A Review of Growth Mechanism - Wang, Ting; Ren, Keliang; He, Miao; Dong, Wenhao; Xiao, Wei; Pan, Hongyu; Yang, Jia; Yang, Yang; Liu, Ping; Cao, Zhijie; Ma, Xiaobo; Wang, Hailong (Frontiers in Chemistry, 2020)
Lithium Nickel Manganese Cobalt Oxide (NMC) cathodes are of great importance for the development of lithium ion batteries with high energy density. Currently, most commercially available NMC products are polycrystalline secondary particles, which are aggregated by anisotropic primary particles. Although the polycrystalline NMC particles have demonstrated large gravimetric capacity and good rate capabilities, the volumetric energy density, cycling stability as well as production adaptability are not satisfactory. Well-dispersed single-crystalline NMC is therefore proposed to be an alternative solution for further development of high energy density batteries. Various techniques have been explored to synthesize the single-crystalline NMC product, but the fundamental mechanisms behind these techniques are still fragmented and incoherent. In this manuscript, we start a journey from the fundamental crystal growth theory, compare the crystal growth of NMC among different techniques, and disclose the key factors governing the growth of single-crystalline NMC. We expect that the more generalized growth mechanism drawn from invaluable previous works could enhance the rational design and synthesis of cathode materials with superior energy density.